Positivisasi Hukum Islam dalam Pembinaan Hukum Nasional di Indonesia - Fitriyani Fitriyani; Abd Basir Laupe (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2013)
In the context of Islamic law, the Jakarta Charter was seen as one of the result of the trial BPUPKI, a persuasive source. New Islamic Law becomes authoritative sources (sources of law has been legally binding) in the state administration, when the July 5 Presidential Decree 1959 which recognizes that animates the Jakarta Charter 1945. Islamic law as a legal order that guided and adhered to by the majority of the population and the people of Indonesia is both the law that has been living within the community. It has also become the part of the teachings and beliefs of Islam that exists in the national law as well as the source of guidance and development.